STUDY ON UTILIZATION OF THE SASAK FISH LANDING BASE FACILITY, PASAMAN BARAT DISTRICT WEST SUMATRA PROVINCE - Pipit Yerma Yernis; Syaifuddin Syaifuddin; Romie Jhonnerie (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abtract This research was carried out in June 2019 at the Sasak Fish Landing Base, West Pasaman Regency, West Sumatra Province. The purpose of this study was to obtain information about the type of facility, condition of the facility, capacity, and to find out the level of utilization of the facilities that support the smooth operation of fisheries in PPI Sasak. The method used in this research is a survey method. PPI Sasak is equipped with several facilities such as basic facilities, functional facilities and supporting facilities. The main facilities consist of a pier, port land, harbor pond, PPI road, functional facilities consist of TPI, PPI Sasak office, fish warehouse, ice warehouse, while supporting facilities consist of PPI Sasak official house and post guard. The activities at PPI Sasak are landing of catches, replenishment of supplies, repair and maintenance of fishing gear, mooring of fishing vessels and ship departure activities. All of the facilities at PPI Sasak have been utilized and have been used according to their function. Of all the existing facilities, only the pier, port pool and TPI are calculated for their use. When viewed from the calculation of the level of facility utilization, it shows that the length of the pier for the loading dock is 30 m while the available wharf is 240 m with a utilization rate of 0.0843%. The required pool area from the results of the analysis carried out is 2,346 m2 with an available pool area of 800 m2 with a pool area utilization rate of 0.00293%. While the required pool depth is 1.6 m with the availability of a 3 m pool depth with a utilization rate of 0.5333%, while for the needs of TPI in PPI Sasak it is 291.6 m while the existing TPI area is 384 m, the percentage of utilization of TPI area is 0, 7593%.Keywords: Facilities, Study of Facility Utilization, PPI Sasak,